Sodium‐Glucose Cotransporter 2 Inhibitors for Mesenchymal–Epithelial Transition Inhibitor‐Induced Edema - Takuya Oyakawa; Keita Miura; Nao Muraoka; Kei Iida; Ayano Fujita; Tateaki Naito; Toshiaki Takahashi (Thoracic Cancer)
ABSTRACT The effects of sodium‐glucose cotransporter 2 (SGLT2) inhibitors on mesenchymal‐epithelial transition factor (MET) inhibitor‐induced edema remain unclear. In a patient with tepotinib‐induced edema and an N‐terminal pro‐brain natriuretic peptide (NTproBNP) level ≥ 300 pg/mL, the addition of empagliflozin to loop diuretics reduced the edema. This suggests that empagliflozin may be a treatment option for MET inhibitor‐induced edema.